The Execution of the Administrative Court’s Decision; Looking for Its Justice and Legal Certainty - Ayuk Hardani (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The execution of the Administrative Court’s decisions seems floating, and there is no final settlement. The implementation of the decision of the State Administrative judge is entirely left to the awareness of the administration official or institution. The problem is that the officials are lack of awareness due to the less supervision by a higher institution like the House of Representatives.Purpose/Objective Study: This article aims to find out the execution to carry out the Administrative court and Administrative court decisions that can provide a sense of justice and legal certainty to the public.Design/Methodology/Approach: The study in this article uses a doctrinal approach with secondary data sourced from books and journals, and is presented using a qualitative method.Findings: The study showed that the execution of the court’s decision only emphasizes the sense of self-respect and legal awareness of the Administrative officials and there has been no application of forced efforts against Administrative officials if they do not implement it. Administrative actions must be following the principles of a legal constitution dominated by the norms of public policy to prevent acts of abuse of authority from higher powers.